Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2147/ott.s259616
|View full text |Cite
|
Sign up to set email alerts
|

<p>Three Novel <em>EGFR</em> Mutations (750_758del, I759S, T751_I759delinsS) in One Patient with Metastatic Non-Small Cell Lung Cancer Responding to Osimertinib: A Case Report</p>

Abstract: Generations of epidermal growth factor receptor tyrosine kinase inhibitors ( EGFR -TKIs) can significantly improve the outcome of EGFR -positive NSCLC patients. However, acquired TKIs-resistant mutations are inevitable. Except the common EGFR alterations, more and more rare mutations are revealed by next-generation sequencing (NGS), the clinical significance of which are still unclear. Here, we report an advanced lung adenocarcinoma patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The lower detection rate (16.7%) of EGFR exon 20 p.T790M may have resulted in shorter PFS in a previously reported study 9 . A case report showed a patient had PFS 7.0 months to icotinib and had resistant mutation T751_I759delinsS after icotinib treatment 10 . The patient had no response to three combinations with chemotherapy, bevacizumab and erlotinib but had a good response to osimertinib for 16 months.…”
Section: Discussionmentioning
confidence: 85%
“…The lower detection rate (16.7%) of EGFR exon 20 p.T790M may have resulted in shorter PFS in a previously reported study 9 . A case report showed a patient had PFS 7.0 months to icotinib and had resistant mutation T751_I759delinsS after icotinib treatment 10 . The patient had no response to three combinations with chemotherapy, bevacizumab and erlotinib but had a good response to osimertinib for 16 months.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, 10 mM osimertinib induced an EGFR phosphorylation inhibition in the YU-1099 cell line, and the inhibitory concentration for YU-1092 was between 30 and 100 nM. Notably the concentrations that inhibited phosphorylation were used to suppress the proliferation of both cell lines ( 20 ). An in-vivo study in the LC-F-29 EGFR G719A;S768I patient-derived xenograft (PDX) model found a significant shrinkage in tumor size ((>100) 45%, p<0.001 at day 14, versus the control group) ( 19 ).…”
Section: The Efficacy Of Osimertinib In Nsclc Patients With Uncommon ...mentioning
confidence: 99%
“…A few studies also showed the efficacy of osimertinib in NSCLC patients with uncommon mutations other than G719X, L861Q, and S768I. A study performed in Nanjing, China presented the first case of patients with novel and rare mutations 750_758del, I759S, and T751_I759delinsS, and durable clinical remission was achieved with the standard dose of osimertinib therapy ( 20 ). Notably, the patient had intractable terminal NSCLC but experienced a prolonged 52-week overall survival with Osimertinib ( 20 ).…”
Section: The Efficacy Of Osimertinib In Nsclc Patients With Uncommon ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A CNS recurrence following firstand second-generation TKIs occurs in 40% of patients due to the limited ability to cross the BBB and the development of resistant mechanisms. In this regard, the third-generation TKI osimertinib has shown a higher penetration through the BBB (CSF level 7.51 and 25.2 nmol/L when administered at 160 mg/day and 300 mg bid, respectively) and now is considered the first-line therapy in LM from EGFR-mutated NSCLC based on the results of several studies [115][116][117][118][119][120][121][122][123], regardless of T790 mutation status [121] (Table 4). The studies reported an intracranial response rate of 20-62%, a median PFS of 7.2-17.2 months, a median OS of 11-18 months and a rapid neurological improvement in the majority of patients [118], as well as a clearance of CSF from neoplastic cells in 28% [117].…”
Section: Lm From Egfr-mutated Nsclcmentioning
confidence: 99%